Hyperoodon Lacépède 1804 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Hyperoodon Lacépède 1804 Hyperoodon Lacépède 1804, Hist. Nat. Cetacees: xliv, 319. Type Species: Hyperoodon butskopf Lacépède 1804 Synonyms: Anodon Wagler 1830; Chaenodelphinus Eschricht 1843; Heterodon Blainville in Desmarest 1817; Lagenocetus Gray 1863; Uranodon Illiger 1811. Species and subspecies: 2 species in 2 subgenera: Subgenus Hyperoodon (Hyperoodon) Lacépède 1804 Subgenus Hyperoodon (Frasercetus) Moore 1968 Species Hyperoodon (Hyperoodon) ampullatus (Forster 1770) Species Hyperoodon (Frasercetus) planifrons Flower 1882 Discussion: Includes Frasercetus Moore, 1968 as a subgenus. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 740, DOI: 10.5281/zenodo.7316519